2021
DOI: 10.22146/jtbb.59235
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Bacterial Isolates from Straw Mushroom Cultivation Medium against Phytopathogenic Fungi

Abstract: Several bacteria were isolated from straw mushroom (Volvariella volvacea) cultivation medium. There are three potential isolates previously characterized and has growth inhibition effect against V. volvacea. This screening result lead to the further study about the inhibition activity against phytopathogenic fungi. The aim of this research is to investigate the antifungal activity of three bacterial isolates against three phytopathogenic fungi and identification of the bacteria. The method used in this study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…(Bacillus siamensis). Studies have confirmed the antibacterial, antifungal and anticancer activities of bis(2-ethylhexyl) phthalate [29,30].…”
Section: Gc-ms Analysis Of the Most Active Fractionmentioning
confidence: 81%
See 1 more Smart Citation
“…(Bacillus siamensis). Studies have confirmed the antibacterial, antifungal and anticancer activities of bis(2-ethylhexyl) phthalate [29,30].…”
Section: Gc-ms Analysis Of the Most Active Fractionmentioning
confidence: 81%
“…Among the confirmed three (3) major compounds is bis(2-ethylhexyl) phthalate, a phthalate ester at Retention time (Rt) of 18.29 and peak area (%) of 33.8. Masrukhin et al [29] similarly reported bis(2-ethylhexyl) phthalate as a major compound from the GC-MS profile of active compounds in the ethyl-acetate extract of a Bacillus spp. (Bacillus siamensis).…”
Section: Gc-ms Analysis Of the Most Active Fractionmentioning
confidence: 99%
“…The crude enzyme from B. velezensis CE 100 degraded the cell wall of C. gloeosporioides, inhibiting spore germination and mycelial growth by 99.3% and 33.6% at 100 µL mL -1 , respectively (Choub et al 2021). Bacillus siamensis C3.8 has inhibitory activity against phytopathogenic fungi such as C. gloeosporioides (Masrukhin et al 2021). B. siamensis H30-3 demonstrated antifungal activities in vitro against C. higginsianum, thereby preventing anthracnose disease in Chinese cabbage (Lee et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…E-15-heptadecenal and E-14-hexadecenal are reported to be involved in antifungal activity. E-15-heptaedecenal is found in the B. siamensis active compound profle which is allegedly involved in antimicrobial Antimicrobe [47][48][49]; antitumor [50] activity of B. siamensis C.38 against some phytopathogenic fungi [32], while E-14-hexadecenal is the antifungal bioactive compound found in the endophytic fungi Pseudarthria viscida (L.) [25,55]. 1-Heneicosanol is the longchain fatty alcohol which is reported to have antimicrobial activity against some pathogenic bacteria.…”
Section: Profling Of the Active Compoundmentioning
confidence: 99%